The Impact of Artificial Intelligence on the Career Positioning of Accounting Personnel in Accounting Applications - Duan, Quanhu (Journal of Theory and Practice of Management Science, 2024)
With the rapid development of society, the accelerated progress of science and technology, artificial intelligence technology appeared, more and more applied in a number of fields, making the daily life and production mode of human beings brought earth-shaking changes, and create value for the society. Artificial intelligence technology as a new technology, like a double-edged sword, can more scientific and reasonable processing of financial information, greatly improving the accuracy of accounting information. Promote the development of accounting industry, but it will also cause the risk of unemployment for accounting personnel, accounting function is replaced. Under the background of artificial intelligence accounting application, this paper analyzes the dilemma caused by accounting industry and accounting personnel, and thinks about what professional qualities accounting personnel should have in the transformation of occupation positioning under this background.